Engineering investigation on large deformation properties of a thermoplastic sheet - Tan, Yik Long (2016)
The use of structural calculation software based on finite-element analysis is nowadays a common practice when designing new industrial products. In order to make an adequate prediction of the service behavior of plastic components, it is necessary to carry out appropriate analysis when working with the software. ANSYS Parametric Design Language (APDL) is an important tool to perform finite element analysis to predict how the product will react in the real world situation. This research paper is focused on to investigate deformation properties of thermoplastic sheet. The investigation will be done through simulation approach, which is by using ANSYS APDL to perform the finite element analysis. The material that is going to be tested is polypropylene, and the testing standard will be followed the standard ASTM D638. The simulation results will be collected and interpreted to determine the de-formation properties and the service behavior of the material.